2014
DOI: 10.1590/1414-462x201400030009
|View full text |Cite
|
Sign up to set email alerts
|

O poder de acessar a saúde: uma análise do acesso à saúde na etnia indígena Xukuru do Ororubá, Pesqueira (PE)

Abstract: Cad. Saúde Colet., 2014, Rio de Janeiro, 22 (3): 275-80Resumo O artigo analisou o acesso à saúde indígena em Pernambuco após a criação do Subsistema de Saúde Indígena, hoje gerido pela Secretaria Especial de Saúde Indígena do Ministério da Saúde (MS), tendo como foco o povo indígena Xukuru do Ororubá. A partir da sociologia de Pierre Bourdieu, foi realizado um estudo de caso buscando caracterizar as "relações de poder" como fator dinâmico associado ao acesso, utilizando-se entrevistas, grupos focais, análise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
1
6
0
6
Order By: Relevance
“…Respect for knowledge, inclusion of singularities -cultural issues, values, beliefs of users Jesus, 2012;Azevedo;Gurgel;Tavares, 2014;Carneiro Junior;Crevelim, 2010;Carreira;Rodrigues, 2010;Andrade;Bosi, 2014;Taddeo et al, 2012), -to the needs (Araújo et al, 2013;Burille;Gerhardt, 2014;Campos et al, 2014;Carneiro Junior;Crevelim, 2010;Chagas et al, 2014;Coelho;Jorge;Araújo, 2009;Esposti et al, 2015;Lima et al, 2007;Medeiros et al, 2010;Souza et al, 2008;Souza;Garnelo, 2008;Takemoto;Silva, 2007), and the knowledge of local reality (Carneiro Junior;Crevelim, 2010;Chagas et al, 2014;Coelho;Jorge;Araújo, 2009;Santos et al, 2012;Souza;Garnelo, 2008;Vanderlei;Navarrete, 2013) were identified as important elements to guarantee access. The listening, the bond, the confidence, the sympathy Jesus, 2012;Burille;Gerhardt, 2014;…”
Section: Chart 1 -Systematization Of the Results According To General Aspects Of Publicationmentioning
confidence: 99%
“…Respect for knowledge, inclusion of singularities -cultural issues, values, beliefs of users Jesus, 2012;Azevedo;Gurgel;Tavares, 2014;Carneiro Junior;Crevelim, 2010;Carreira;Rodrigues, 2010;Andrade;Bosi, 2014;Taddeo et al, 2012), -to the needs (Araújo et al, 2013;Burille;Gerhardt, 2014;Campos et al, 2014;Carneiro Junior;Crevelim, 2010;Chagas et al, 2014;Coelho;Jorge;Araújo, 2009;Esposti et al, 2015;Lima et al, 2007;Medeiros et al, 2010;Souza et al, 2008;Souza;Garnelo, 2008;Takemoto;Silva, 2007), and the knowledge of local reality (Carneiro Junior;Crevelim, 2010;Chagas et al, 2014;Coelho;Jorge;Araújo, 2009;Santos et al, 2012;Souza;Garnelo, 2008;Vanderlei;Navarrete, 2013) were identified as important elements to guarantee access. The listening, the bond, the confidence, the sympathy Jesus, 2012;Burille;Gerhardt, 2014;…”
Section: Chart 1 -Systematization Of the Results According To General Aspects Of Publicationmentioning
confidence: 99%
“…Diferentemente da pesquisa realizada acima, Azevedo et al (2014) relata que as dificuldades que o povo Xukuru enfrenta está além do acesso à saúde, como os conflitos locais e sociais que transcendem as barreiras culturais, interferindo na luta pela terra ocupada. Pode se evidenciar que os capitais ativos no campo da saúde indígena (social, cultural, étnico, político e simbólico), especificamente na atenção básica, constituíram recursos de poder associados ao acesso.…”
Section: Principais Dificuldades Enfrentadas Pelos Povos Indígenas Frunclassified
“…It is assumed that the DSEI care model is organized as follows: Health Centers, Health Base, and House of Health of the Indian (CASAI), being the base pole to address the demands of exams for outpatient clinics and hospitals of regional references. 13 It is evidenced that the absence of emergency assistance in São José Village is recurrent due to the health care of the Orukuba Xukuru follow the same logic of the Unified Health System (SUS). It is due to the fact that the DSEI establish basic health actions that attend to the health problems more frequent and less complex.…”
Section: ❖ Traditional Medicine X Biomedical Modelmentioning
confidence: 99%
“…The actions of medium and high complexity are executed in the municipality of Pesqueira or outside it, since they do not exist in São José Village. 13 This reality of indigenous health care reflects a set of precarious conditions, hampering the resolution of health problems in the villages. The search for the city hospital appears as a great obstacle, since the native one reports that there is a considerable distance between the native territory and the city.…”
Section: ❖ Traditional Medicine X Biomedical Modelmentioning
confidence: 99%